2005
DOI: 10.1038/modpathol.3800285
|View full text |Cite
|
Sign up to set email alerts
|

Role of COX-2, thromboxane A2 synthase, and prostaglandin I2 synthase in papillary thyroid carcinoma growth

Abstract: The development of papillary thyroid carcinoma is influenced by many factors including genetic alterations, growth factors, and physical agents such as radiation. Arachidonic acid and its derivatives including prostaglandins (PG) and thromboxane along with the enzymes involved in their synthesis have been shown to influence the growth of various tumors. We analyzed the immunoreactivity for cyclooxygenase-2 (COX-2) and mRNA expression levels of the enzymes COX-2, thromboxane A 2 (TXA 2 ) synthase, and PGI 2 syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 44 publications
2
42
0
5
Order By: Relevance
“…In vitro studies of thyroid cancer cell lines have shown that a selective inhibitor of COX-2, NS-398, can inhibit proliferation (13), and reduce cellular migration and invasion (14). In esophageal cancer, COX-2 expression has also been shown to be associated with anti-apoptosis (15).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of thyroid cancer cell lines have shown that a selective inhibitor of COX-2, NS-398, can inhibit proliferation (13), and reduce cellular migration and invasion (14). In esophageal cancer, COX-2 expression has also been shown to be associated with anti-apoptosis (15).…”
Section: Introductionmentioning
confidence: 99%
“…TxA 2 is a potent vasoconstrictor, mitogen, and platelet activator (9)(10)(11). Increased thromboxane synthase expression and/or elevated levels of TxB 2 , the stable product of TxA 2 , were found in papillary thyroid carcinoma (12), larynx squamous cell carcinoma (13), and renal carcinoma (14). Previously, we reported an increase in thromboxane synthase at mRNA level in renal carcinoma, breast carcinoma, prostate cancer, and uterine cancer when compared with their matched normal tissues in a cancer profiling array (15).…”
Section: Introductionmentioning
confidence: 99%
“…As the TXA 2 -TP axis has been implicated in the development of prostate and breast cancer (20,33,47,94,95), the findings herein suggest that aberrant WT1 regulation of TPα expression may contribute to such cancers and potentially to WT itself. In addition, bearing in mind that the TPα and TPβ isoforms display a number of important functional similarities but also differences in terms of their signalling (6) and regulation including in certain cancers (96,97), coupled with the fact that they are regulated by distinct promoters within the TBXA2R gene, it will be of considerable interest to investigate the expression and transcriptional regulation of TPβ in human cancers, in particular in prostate and breast cancer.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 92%